Comparison version: The Planning and Development of Land Act, 1995, draft September 25, 1995 compared with the Planning, Development and Building Act, 1995, draft August 9, 1995 - Jaffary, Karl. Et al. (Government of the Republic Trinidad and Tobago., 2011)
Reproduction of both draft Acts showing differences in text.
Keywords: Development planning Laws - Trinidad and Tobago, Land development – Legislation, Environmental management, Regional planning, Environmental protection, Sustainable development, Construction - Laws